2018
DOI: 10.3390/nu10081088
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Cognitive Function among Older Community-Dwelling Adults

Abstract: Diet may be an important modifiable risk factor for maintenance of cognitive health in later life. This study aimed at examining associations between common dietary indices and dietary patterns defined by factor analysis and cognitive function in older community-dwelling adults. Dietary information for 1499 participants from the Rancho Bernardo Study was collected in 1988–1992 and used to calculate the alternate Mediterranean diet score, Alternate Healthy Eating Index (AHEI)-2010 score and factor scores derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 79 publications
(91 reference statements)
2
25
0
1
Order By: Relevance
“…Excess consumption of simple sugars and inadequate fiber consumption is associated with the development of dyslipidemia, obesity, and insulin resistance. As Richards et al [48] reported, high sugar and lower protein consumption may lead to insulin resistance and lower cognitive function in older community-dwelling adults. Furthermore, in U3A, inadequate fiber (10.5 g/1000 kcal vs. 14 g/1000 kcal recommended) and high sacharose and lactose (Table 1) consumption are other factors affecting the tCh and LDL-C concentrations as well as a high VFA [3].…”
Section: Discussionmentioning
confidence: 98%
“…Excess consumption of simple sugars and inadequate fiber consumption is associated with the development of dyslipidemia, obesity, and insulin resistance. As Richards et al [48] reported, high sugar and lower protein consumption may lead to insulin resistance and lower cognitive function in older community-dwelling adults. Furthermore, in U3A, inadequate fiber (10.5 g/1000 kcal vs. 14 g/1000 kcal recommended) and high sacharose and lactose (Table 1) consumption are other factors affecting the tCh and LDL-C concentrations as well as a high VFA [3].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies found that diet quality was not associated with cognition [25,26,27,41]. This inconsistency may be attributable to the following reasons.…”
Section: Discussionmentioning
confidence: 95%
“…These differing conclusions could be due to varying fatty acid profiles within the diet. For example, a prospective cohort study from 1988-2016 found that adhering to a Mediterranean diet or a plant based polyunsaturated fatty acid diet increases global cognitive function and executive function support [38]. Whereas another prospective cohort, a higher intake of a Western style diet (typically higher in saturated fats) was correlated with worse cognitive performance on visual spatial learning, long-term memory, and reaction time tasks [39].…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that this study did not categorize fat intake by saturated or unsaturated fats. Previous research has shown the difference that fatty acids can have on cognition [38,39] and cytokine levels [21]. Many of the high fat foods listed were high in saturated fats, with the exception of the omega 3 supplement.…”
Section: Discussionmentioning
confidence: 99%